The Impact of TikTok Usage on University Students’ Academic Performance and Moral Development - Anamta,; Muhammad Adnan Shad,; Dr. Shumaiela Farooqi ,; Dr. Shafqat Rasool, (Dialogue Social Science Review (DSSR), 2025)
This study investigates the effect of TikTok usage on students’ academic performance and moral development at university level. This study used a survey (questionnaire) method to collect the data. The research sample comprised 400 students from the public and private sector universities in Faisalabad, Pakistan. This study’s main objectives were to determine the level of use of TikTok, academic performance and moral development of students of higher level. Find the impact of use of TikTok on academic performance and on moral development and to determine the effect of different variables (age, gender, program faculty and institute) on use of TikTok and moral development. The 21st version of SPSS (Statistical Package for Social Sciences) was utilized for the analysis. In this study descriptive statistics were displayed, and an independent sample t-test and one-way analysis of variance (ANOVA) and regression were used to identify the difference according to gender, age, faculty, degree-level, university and sector. Coefficient results indicated that TikTok and academic performance have a direct correlation while TikTok and moral development have an inverse relationship. Regression results indicated that when level of use of TikTok increases by one unit the academic performance increases by 0.50 units while and moral development decreases by 0.62 units.